Advection Flows‐Enhanced Magnetic Separation for High‐Throughput Bacteria Separation from Undiluted Whole Blood. Issue 34 (25th July 2018) - Jung, Su Hyun; Hahn, Young Ki; Oh, Sein; Kwon, Seyong; Um, Eujin; Choi, Sungyoung; Kang, Joo H.
Abstract: A major challenge to scale up a microfluidic magnetic separator for extracorporeal blood cleansing applications is to overcome low magnetic drag velocity caused by viscous blood components interfering with magnetophoresis. Therefore, there is an unmet need to develop an effective method to position magnetic particles to the area of augmented magnetic flux density gradients while retaining clinically applicable throughput. Here, a magnetophoretic cell separation device, integrated with slanted ridge‐arrays in a microfluidic channel, is reported. The slanted ridges patterned in the microfluidic channels generate spiral flows along the microfluidic channel. The cells bound with magnetic particles follow trajectories of the spiral streamlines and are repeatedly transferred in a transverse direction toward the area adjacent to a ferromagnetic nickel structure, where they are exposed to a highly augmented magnetic force of 7.68 µN that is much greater than the force (0.35 pN) at the side of the channel furthest from the nickel structure. With this approach, 91.68% ± 2.18% of Escherichia coli (E. coli) bound with magnetic nanoparticles are successfully separated from undiluted whole blood at a flow rate of 0.6 mL h −1 in a single microfluidic channel, whereas only 23.98% ± 6.59% of E. coli are depleted in the conventional microfluidic device. Abstract : Advective spiral flows induced by asymmetric slanted ridge array significantly improve the magnetic separation efficiency in whole blood. The spiral rotational flows repeatedly deliver the magnetic particle‐bound cells to the area of stronger magnetic force, where the magnetic particles are effectively separated. This strategy overcomes the current limitation of microfluidic magnetic separation in viscous fluids, such as whole blood.